The Influence Of Menu Variations, Prices And Atmosphere Of The Place On Consumer Satisfaction At Commonroom Coffee Cilandak - Kusumaningrum, Anisa Putri; Pradini, Gagih; Eranti, Ardissa Dwi; Supriyadi, Edouard Aryadi; Wicaksono, Ajie (CV ODIS, 2023)
This study aims to (a) determine the variety of menus, prices and atmosphere of the place affect consumer satisfaction at the Commonroom Coffee Cilandak café (b) to determine the variance of menu, price and atmosphere of the place simultaneously on consumer satisfaction at the Commonroom Coffee Cilandak café (c) to find out which variables affect consumer satisfaction at the Commonroom Coffee Cilandak café. The research sample was 138 respondents who were buyers at Commonroom Cofee Cilandak, the study used quantitative analysis methods of data collection using questionnaires. The results of the study are menu variations, prices and atmosphere of the place produce data that have a positive effect together and significantly on consumer satisfaction at Commonroom Coffee Cilandak